Numerical and Experimental Analysis in the Production of a Solar Still. Issue 1 (January 2021) - Chávez, S; Terres, H; Lizardi, A; López, R; Lara, A; Vaca, M
Abstract: In this work, a numerical and experimental study is shown for a single slope solar still with internal reflectors and a finned system at the absorber plate, in it 30 experimental tests were made with 3 L of water, for which temperature measurements were obtained, mainly at the glass cover, the absorber plate, fluid and at the environment, as well as the incident solar radiation, the experimental information was obtained through ADAMS modules, type K thermocouples and a pyranometer, besides the distillate volume was measured with measuring cylinders. From the experimental data, a model was constructed to understand the effect of solar radiation and fluid temperature on distillate production. As a result, for this experiment a cubic function that describes de distillate volume behaviour was found, which only depends on the solar radiation and the official time, this equation has at least a 6% error on average regarding to the experimental distillate volume.